Implementasi Program KKN untuk Penguatan Literasi, Digitalisasi UMKM, dan Moderasi Sosial di Desa Ndokum Siroga - Rusma Riansyah; Dahri Aziz; Servina Rahayu; Annisa Salsabila; Uqbatul Khoir Rambe (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
Community service through the Kuliah Kerja Nyata (KKN) program in Ndokum Siroga Village aims to strengthen literacy, digitalize micro, small, and medium enterprises (MSMEs), and promote social moderation. This program was carried out over 30 days, involving 29 students from various disciplines. The methods used included literacy training for elementary school students to increase reading interest, digital marketing workshops to optimize MSMEs' market potential, and social dialogue sessions to facilitate communication among community members. The results showed a 60% increase in the reading interest of elementary school students, with activities encouraging reading habits outside school hours. Additionally, digitalization was successfully applied to 12 MSMEs, which are now able to operate their businesses online, expanding market reach and increasing revenue. The application of social moderation also showed positive results, with increased interfaith harmony reflected in joint social activities involving various community elements. This program successfully addressed existing community challenges such as low reading interest, limited access to MSME markets, and potential social tensions. The integrated approach combining education, economic empowerment, and social cohesion made a significant contribution to sustainable village development. This program is not only beneficial to the people of Ndokum Siroga Village but also serves as a model that can be replicated in other villages with similar challenges to achieve inclusive and sustainable development.